A phase field method to simulate crack nucleation and propagation in strongly heterogeneous materials from direct imaging of their microstructure. (May 2015) - Nguyen, T.T.; Yvonnet, J.; Zhu, Q.-Z.; Bornert, M.; Chateau, C.
Graphical abstract: Highlights: Application of the phase field (PP) to microcracking in concrete microstructures. Crack initiation and propagation in complex voxel-based models of microstructures. An enhanced algorithm within PP is proposed to increase the load increments. Abstract: In this work, crack initiation and propagation in 2D and 3D highly heterogeneous materials models, such as those obtained by micro-CT imagery of cementitious materials, is investigated for the first time by means of the phase field method. A shifted strain split operator algorithm is proposed to handle unilateral contact within cracks in a very efficient manner. The various advantages of the phase field method for voxel-based models are discussed. More specifically, we show that the resolution related to the initial image and thus to meshes for discretizing the same microstructure does not significantly affect the simulated crack path.